Marketing Management Pricing Strategy - Rezki, Rezki (Journal Development Manecos, 2023)
This article discusses marketing strategies, which are closely related to market prices, where the price is the amount of money that must be spent by consumers to get the products or services they buy to meet their needs or wants and are generally expressed in monetary units. Therefore, the purpose of this article is that it is hoped that later readers will be able to understand matters relating to market strategy, pricing objectives, pricing methods, pricing strategies.